Patterns of Islet Cell Dysmaturation Syndrome among Saudi Infants - Abdulmoein E. Al-Agha; Yasir S. Jamal; Ali H. Ocheltree; Mazen O. Kurdi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Islet cell dysmaturation syndrome is the most common cause of hypoglycemia in early infancy. A retrospective study patterns of Islet cell dysmaturation syndrome among infants presenting with hypoglycemiais on 28 patients from 2007-2011, follow-up mean 12.8 ± 6.8 months, was conducted. Diagnosed based on high intravenous glucose requirement, high insulin/glucose ratio, negative urinary ketones, and duration of repeated episodes of hypoglycemia more than 6 months. Enrolled patients underwent neurological assessment, both radiological and electrophysiological. Patients who failed medical therapy underwent near-total pancreatectomy. Transient hypoglycemia of infancy found in 16 patients 57% and islet cell dysmaturation syndrome in 43%. Eight of them presented with hypoglycemic seizures. Most of the cohort required near-total pancreatectomy 58.3%. Three pancreatectomized patients developed insulin dependent diabetes mellitus. Two medically treated patients developed insulin-dependent diabetes mellitus and weight gain. The majority (91.7%) was followed-up to at least 1 year of age (follow-up was 14.8 ± 6 months). Four suffered from repeated hypoglycemic seizures during follow-up. Early intervention is necessary to avoid neurological damage. Surgically and medically treated patients are at risk of developing insulin-dependent diabetes mellitus. Morbidity in survivors of Islet cell dysmaturation syndrome is high and calls for greater awareness, early diagnosis and genetic counseling.